Regenerasi Tanaman Kitolod (Hippobroma longiflora (L.) G.Don) pada Kultur In Vitro: Plant Regeneration of Kitolod (Hippobroma longiflora (L.) G.Don) in In Vitro Culture - Nur`Aeni, Fitri; Ratnadewi, Diah; ., Sumaryono (Jurnal Sumberdaya Hayati, 2022)
Kitolod (Hippobroma longiflora (L.) G. Don) is a wild plant. Its flower is widely used as a traditional medicine.When this plant is utilized more intensively, there may be a shortage of the plant due to the lack of seed sources. This study aimed to obtain the best techniques and culture conditions for in vitro propagation of kitolod to provide a large number of planting materials. The experiments were arranged using a completely randomized design with two treatment factors and 10 replications for all experiments except in shoot rooting. Leaves and petioles were used as explant sources. Various combinations of benzilamino purine (BAP) and naphtalene acetic acid (NAA) were applied. Leaf explants in Murashige and Skoog (MS) medium enriched with 1 mg/L BAP and 0.1 mg/L NAA combination produced the highest number of adventitious shoots per explant, but 2 mg/L BAP + 0.1 mg/L NAA was more effective for shoot initiation and multiplication. The latter medium was also able to produce the tallest shoots, and presented 75% of successful rate over the acclimatization period. The best rooting was provided by MS medium added with 0.5-1.0 mg/L NAA.